Pendampingan pastoral bagi pasangan suami istri yang mengalami konflik yang berakar pada kemarahan dan stress dalam pernikahan - Bun Hui Fuaddin (TE DEUM (Jurnal Teologi dan Pengembangan Pelayanan), 2021)
This article is a literature study that describes the concept of pastoral care for married couples who experience conflict in marriage. To explain this, the author presents various information from primary sources in the form of interviews with married couples who experience conflict in marriage. The author also presents information from secondary sources related to the research topic which is then described descriptively. From the research conducted, the author found that the conflict experienced by the husband was rooted in anger and stress. Married couples who experience anger and stress in marriage need pastoral assistance in dealing with situations in their married life, because it is not easy to resolve these two things well and healthily. Pastoral counseling to deal with married couples who experience anger and stress in marriage needs to be given since premarital counseling.